Persistent indolent pancolonic marginal zone lymphoma of MALT-type with plasmacytic differentiation - A rare post-transplant lymphoma? - Joanna M. Chaffin; Natasha M. Savage; Suash Sharma; Locke J. Bryan; Mark Raffeld; Elaine S. Jaffe (Elsevier, 2017)
Marginal zone lymphoma of mucosa-associated lymphoid tissue (MALT lymphoma) is associated with chronic inflammatory disorders. We present an indolent pancolonic MALT lymphoma occurring in a 39-year-old female with history of autoimmune hepatitis requiring liver transplant in 1997 and ulcerative colitis diagnosed in 2004. Random biopsies from a grossly unremarkable surveillance colonoscopy in 2015 revealed a dense monomorphic plasmacytoid infiltrate causing expansion of lamina propria without significant crypt infiltration or destruction. These cells were positive for CD79a and CD138 and showed lambda restriction; however, CD20, CD43, CD56, HHV8, and EBER were negative. A similar pancolonic infiltrate was identified in all prior colorectal biopsies from 2010 and 2012 upon retrospective review. Subsequent computed tomography of the abdomen revealed no bowel wall thickening nor enlarged lymph nodes. Bone marrow revealed involvement consistent with stage IV disease. Biopsies from 2010 and 2015 demonstrated clonal immunoglobulin gene rearrangement. MYD88 mutation was not detected. The overall features were indicative of MALT lymphoma. Although low-grade B-cell lymphomas are not considered part of the post-transplant lymphoproliferative disorder spectrum, such cases have been reported, and are typically EBV-negative. Patient underwent treatment with pentostatin for her MALT lymphoma reaching a sustained remission despite additional immunosuppression for resurgent hepatic dysfunction. To our knowledge, this is the first reported case of EBV-negative pancolonic MALT lymphoma with plasmacytic differentiation post liver transplant presenting in an indolent, asymptomatic fashion with persistence for greater than five years successfully managed without compromising the patient's liver transplant.